2023
DOI: 10.1192/bjo.2023.512
|View full text |Cite
|
Sign up to set email alerts
|

Attention-deficit hyperactivity disorder diagnoses and prescriptions in UK primary care, 2000–2018: population-based cohort study

Abstract: Background Rates of diagnosed attention-deficit hyperactivity disorder (ADHD) may be increasing in the UK. Aims Estimate incidence and prevalence of ADHD diagnoses and ADHD prescriptions in UK adults and children in primary care. Method We conducted a cohort study using IQVIA Medical Research Data, a UK primary care database. Rates of ADHD diagnoses and ADHD prescriptions were calculated between 2000 and 2018 for individuals aged 3–99 years, analysed by age, gender, soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The number of young people being diagnosed with a neurodevelopmental condition (NDC), has dramatically increased in recent years [1]. Specifically, there has been a substantial upsurge in the number of children and adolescents being referred to mental health services for suspected Attention Deficit Hyperactivity Disorder (ADHD), Autism and Tic Disorders (i.e., Transient or Chronic Tic Disorders and Tourette's Syndrome), without an associated intellectual disability [2,3,4,5,6]. While many of these conditions were previously conceptualized as being limited to childhood, they are now known to be lifelong [7].…”
Section: Introductionmentioning
confidence: 99%
“…The number of young people being diagnosed with a neurodevelopmental condition (NDC), has dramatically increased in recent years [1]. Specifically, there has been a substantial upsurge in the number of children and adolescents being referred to mental health services for suspected Attention Deficit Hyperactivity Disorder (ADHD), Autism and Tic Disorders (i.e., Transient or Chronic Tic Disorders and Tourette's Syndrome), without an associated intellectual disability [2,3,4,5,6]. While many of these conditions were previously conceptualized as being limited to childhood, they are now known to be lifelong [7].…”
Section: Introductionmentioning
confidence: 99%
“…Based on administrative data, Holden estimated a childhood UK prevalence of 0.55% (0.93% in boys, and 0.15% in girls [ 5 ]. Additionally, a more recent retrospective cohort study in the UK indicated that the childhood prevalence of ADHD was 1.8% among boys and 0.4% among girls [ 6 ]. Due to increased knowledge, recognition, and diagnosis, the prevalence of ADHD amongst children in the UK has increased in recent years [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%